In Silico Sperm Proteome Analysis to Investigate DNA Repair Mechanisms in Varicocele Patients - Finelli, Renata; Darbandi, Sara; Pushparaj, Peter Natesan; Henkel, Ralf; Ko, Edmund; Agarwal, Ashok (Frontiers in Endocrinology, 2021)
Varicocele, a condition associated with increased oxidative stress, negatively affects sperm DNA integrity and reduces pregnancy rates. However, the molecular mechanisms related to DNA integrity, damage, and repair in varicocele patients remain unclear. This study aimed to analyze the sperm proteomics data from varicocele patients to determine the role of DNA repair molecular mechanisms in varicocele-related infertility by combining a proteomics in silico approach with wet-laboratory techniques. Proteomics data previously generated from varicocele patients (n=50) and fertile controls (n=10) attending the Andrology Center were reanalyzed using bioinformatics tools, including the WEB-based Gene SeT AnaLysis Toolkit, Open Target Platform, and Ingenuity Pathway Analysis (IPA), to identify differentially expressed proteins (DEPs) involved in DNA repair. Subsequently, selected DEPs in spermatozoa were validated using western blotting on varicocele (n = 13) and fertile control (n = 5) samples. We identified 99 DEPs mainly involved in male reproductive system disease (n=66) and male infertility (n=47). IPA analysis identified five proteins (fatty acid synthase [FASN], myeloperoxidase [MPO], mitochondrial aconitate hydratase [ACO2], nucleoporin 93 [NUP93], and 26S proteasome non-ATPase regulatory subunit 14 [PSMD14]) associated with DNA repair deficiency, which showed altered expression in varicocele (P <0.03). We validated ACO2 downregulation (fold change=0.37, change%=-62.7%, P=0.0001) and FASN overexpression (fold change = 4.04, change %= 303.7%, P = 0.014) in men with varicocele compared to controls. This study combined a unique in silico approach with an in vitro validation of the molecular mechanisms that may be responsible for varicocele-associated infertility. We identified ACO2 and FASN as possible proteins involved in DNA repair, whose altered expression may contribute to DNA damage in varicocele pathophysiology.